2014
DOI: 10.5603/piap.2014.0074
|View full text |Cite
|
Sign up to set email alerts
|

Mikobakterioza u Chorych na Mukowiscydozę—Opis Trzech Przypadków

Abstract: Introduction: In the 19th and 20th centuries the cerebellum was mainly associated with human somato-motoric function, but later studies proved that its activity is much more complex. The cerebellum participates in the regulation of cognitive functions such as planning, verbal fluency, operational memory and abstract thinking. Case studies: We present the cases of two patients with cerebel-lar hyperplasia and a description of the functions of their working memory before and after neurosurgical treatment. Conclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…Growing evidence exists in the literature that CF is a risk factor for NTMLD [39][40][41]. The study concerning 16 153 CF patients above 12 years of age, conducted by Adjemian et al [40] revealed at least one NTM isolation in between 2010 and 2014 in 20% of them.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence exists in the literature that CF is a risk factor for NTMLD [39][40][41]. The study concerning 16 153 CF patients above 12 years of age, conducted by Adjemian et al [40] revealed at least one NTM isolation in between 2010 and 2014 in 20% of them.…”
Section: Discussionmentioning
confidence: 99%
“…W aktualnym numerze "Pneumonologii i Alergologii Polskiej" znajdują się 2 prace na temat mikobakteriozy płuc. Jedna dotyczy chorych z mukowiscydozą i dobrze obrazuje trudności rozpoznawcze i ryzyko, które wiąże się z zakażeniem NTM w tej chorobie [27]. Druga praca ma niezwykle nowatorski charakter.…”
unclassified